Characterization of Littoral Macrozoobenthos Communities of the Kuybyshev Reservoir in the Area of Kazan - G.S. Tarasov (Učënye Zapiski Kazanskogo Universiteta. Seriâ Estestvennye Nauki, 2016)
Seasonal fluctuations in the species composition and quantitative indices of benthic communities in the littoral zone of the Kuybyshev Reservoir were investigated near the village of Staroe Arakchino in the summer–autumn season of 2014. On the whole, 40 taxa of macrozoobenthos were identified during the period of investigation. These taxa belong to the following groups of invertebrates: the phyllum of Mollusca (the classes of Bivalvia and Gastropoda), the class of Insecta (the orders of Diptera, Ephemer-optera, Odonata), and the phyllum of Annelida (the classes of Oligochaeta and Hirudinea). The highest species diversity was observed for insects and mollusks species. There was a reduction in the species diversity compared to the data of a similar research performed in 2010–2013. Zoobenthos samples were characterized by the absence of some orders of insects (Trichoptera, Coleoptera larvae and adults) and Maxillopoda. The abundance and biomass indices of macrozoobenthos in 2014 were lower than the same indices in 2010–2013. Two classes of mollusks (Gastropoda and Bivalvia) formed the dominant group in abundance and biomass. The significant influence on the quantitative indices was produced by Viviparus viviparus (L., 1758), as well as by such invasive species as Dreissena polymorpha (Pallas, 1771) and Lithoglyphus naticoides (Pfeiffer, 1828).